A Magnetospheric Driver of Westward Traveling Surge: Plasma‐Sheet Bubble - Dong Wei; Fei Zhang; Jian Yang; Wenrui Wang; Weiqin Sun; Jun Cui; Vassilis Angelopoulos (Geophysical Research Letters)
Abstract The westward traveling surge (WTS) is one of the most significant manifestations of auroral substorms. The formation and evolution of WTS are the key to understanding the dynamics of substorm. However, the generation mechanism of WTS remains unclear. This study investigates the magnetospheric driver of WTS using numerical simulations of the Inertialized Rice Convection Model. We model a typical WTS event by specifying a low‐entropy bubble injection from the magnetotail. The simulated characteristics of the WTS are consistent with typical observed features. Simulation confirms that the bubble injection creates an intense upward Region‐1 field‐aligned current to flow into the ionosphere, which is responsible for the prominent auroral structure. Moreover, the calculated speed of westward expansion of the bubble in the magnetosphere agrees very well with the speed of the westward surge in the ionosphere. Therefore, the plasma‐sheet bubble is believed to be a possible magnetospheric source of the WTS.